STUDY OF HILAL’S CONTRAST USING INFRARED FILTER IN DAYLIGHT HILAL OBSERVATION - Firdaus, Muhammad Dimas; Rakhmadi, Arwin Juli; Hidayat, Muhammad; Putraga, Hariyadi (Proceeding International Seminar of Islamic Studies, 2023)
Hilal observation has already undergone a very significant development of techniques. From daytime observations, up to the uses of various instruments that can support the success of observations. One of the routine activities carried out by the Falak Science Observatory of Muhammadiyah University of North Sumatra is daytime hilal observation.  The hilal observation conducted by OIF UMSU uses an infrared filter instrument that can transmit light at infrared wavelengths and filter light at other wavelengths. This research tries to compare the contrast of daylight hilal images taken using filters and not using filters.The results obtained from the experiments carried out resulted in a contrast value using an infrared filter is 129% using Weber contrast analysis, and 4% using Michelson contrast analysis.